2016
DOI: 10.3847/0004-637x/825/1/73
|View full text |Cite
|
Sign up to set email alerts
|

A Statistical Analysis of the Accuracy of the Digitized Magnitudes of Photometric Plates on the Timescale of Decades With an Application to the Century-Long Light Curve of Kic 8462852

Abstract: We present a statistical analysis of the accuracy of the digitized magnitudes of photometric plates on the time scale of decades. In our examination of archival Johnson B photometry from the Harvard DASCH archive, we find a median RMS scatter of lightcurves of order 0.15mag over the range B ∼ 9 − 17 for all calibrations. Slight underlying systematics (trends or flux discontinuities) are on a level of 0.2mag per century for the majority of constant stars. These historic data can be unambiguously used for proce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 31 publications
0
22
1
Order By: Relevance
“…This tendency refutes the apparent brightening of AR Sco in DASCH. It is worth noting that there has been a recent disagreement between Schaefer (2016) and Hippke et al (2016) over whether the Damons North Blue series exhibits a flux discontinuity relative to the rest of the DASCH light curve. 5 We take no position on their debate.…”
Section: The Apparent Long-term Brightening Is An Instrumental Effectmentioning
confidence: 99%
“…This tendency refutes the apparent brightening of AR Sco in DASCH. It is worth noting that there has been a recent disagreement between Schaefer (2016) and Hippke et al (2016) over whether the Damons North Blue series exhibits a flux discontinuity relative to the rest of the DASCH light curve. 5 We take no position on their debate.…”
Section: The Apparent Long-term Brightening Is An Instrumental Effectmentioning
confidence: 99%
“…Evidence was found that the light from the star has been dimming over century timescales, with a 16% decrease in brightness from 1890 to 1980 (Schaefer 2016), the so-called secular dimming. This secular dimming remains controversial, since analysis of the same archival data found no evidence for the dimming (Hippke et al 2016), and a different set of archival data also found no evidence for secular dimming (Hippke et al 2017). Nevertheless, reanalysis of the Kepler data, which had been baselined to remove any long-term trends in the original analysis, showed evidence for a long-term dimming trend of ∼ 3% over a 4 year timescale (Montet & Simon 2016).…”
Section: Introductionmentioning
confidence: 97%
“…KIC 8462852 is an F3V star located at about 454±35 pc away from us (Hippke et al 2016). The Kepler Spacecraft photometric data revealed an enigmatic lightcurve for this star, with erratic, up to ∼20% deep, stellar flux dimmings (Boyajian et al 2016).…”
Section: Introductionmentioning
confidence: 99%